Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Mettre l'amitié au premier plan : passés et futurs féministes - Roseneil, Sasha (Nouvelles Questions Féministes, 2011)
L'amitié est un champ d'études peu exploré et cependant d'importance vitale pour les études genre et féministes. En revisitant l'histoire des écrits féministes sur les amitiés entre femmes, l'article explore l'importance qui est donnée à l'amitié par les premières générations de féministes tout au long du XXe siècle. En se concentrant sur les considérations polémiques, théoriques et empiriques à l'égard de l'amitié, l'article suggère que l'amitié a été historiquement fondamentale pour les politiques, les identités et les communautés féministes. Il conclut par un argument en faveur de la place centrale de l'amitié - avec le même sexe, hommes et femmes, mais aussi entre les sexes - dans les programmes de recherche féministes, aujourd'hui et dans l'avenir. Le prisme de l'amitié conduit à une remise en question radicale de l'hétéronormativité des sciences sociales, et attire notre attention sur les façons dont la vie intime a été reconfigurée au début du XXIe siècle.
https://www.jstor.org/stable/41346017 Traduction de : Sasha Roseneil (2006). « Foregrounding Friendship : Feminist Pasts, Feminist Futures ». In Kathy Davis, Mary Evans & Judith Lorber (Éds) Handbook of Gender Women’s Studies, (pp. 322-341). Londres : SAGE Publications.
Keywords: 1900-1999; amitié; approches et analyses; care; cours; cycles supérieurs; discipline; fem7000; genre; histoire de l'art; histoire et politique; hétéronormativité; hétérosexisme; intimité; lesbianisme; littérature française; littérature lesbienne; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires